(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The aspect of the private universities is that they aregenerally prone to be compared with good government universities, while manyof them are unfortunately functioning at low standards. Recently, some privateeducational institutions in India have been investing significant amount offunds in courses which are of contemporary significance. Many of those managingsuch educational institutions are retired teachers from governmentinstitutions, who are making sincere efforts in building up these institutions.